Armageddon in retrospect : and other new and unpublished writings on war and peace - Vonnegut, Kurt.; Vintage (London : Vintage Books, 2009)
A collection of twelve writings by twentieth-century American novelist Kurt Vonnegut that reflect war and peace, including his reflections on the destruction of Dresden during World War II.
Letter from PFC Kurt Vonnegut Jr. to his family, May 29, 1945 -- Kurt Vonnegut at Clowes Hall, Indianapolis, April 27, 2007 -- Wailing shall be in the streets -- Great day -- Guns before butter -- Happy birthday, 1951 -- Brighten up -- The unicorn trap -- Unknown soldier -- Spoils -- Just you and me, Sammy -- The commandant's desk -- Armageddon in retrospect.
Adult
Keywords: Peace -- Literary collections; War -- Literary collections